2017
DOI: 10.3892/mmr.2017.7922
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered recombinant adenovirus expressing interleukin‑2 for hepatocellular carcinoma therapy

Abstract: Regulatory and effector T cells possess immunological cytotoxicity for tumor cells in the tumor microenvironment during tumor progression and are the primary suppressors inhuman cancer therapy. Interleukin‑2 (IL‑2) is an anticancer cytokine, which triggers human innate and adaptive immunity by stimulating T cell propagation and lymphocyte infiltration into tumor sites. IL‑2 has been used successfully for cancer therapy. Recombinant adenovirus expressing IL‑2 (rAd‑IL‑2) injection is a gene therapy agent that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Furthermore, an increasing amount of research has reported that oncolytic adenoviruses are capable of infecting and expressing exogenous functional genes with no target cells. The functional/effector genes can be classified in four categories by their functions: (1) Tumor-suppressor gene (51, 52); (2) Cytotoxic gene; (3) Immune-modulating gene (53); (4) Tumor-antigens (54). The following is the detailed introduction of genes carried by oncolytic adenoviral vectors for HCC treatment.…”
Section: Genetic Modifications Of Oncolytic Adenovirusmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, an increasing amount of research has reported that oncolytic adenoviruses are capable of infecting and expressing exogenous functional genes with no target cells. The functional/effector genes can be classified in four categories by their functions: (1) Tumor-suppressor gene (51, 52); (2) Cytotoxic gene; (3) Immune-modulating gene (53); (4) Tumor-antigens (54). The following is the detailed introduction of genes carried by oncolytic adenoviral vectors for HCC treatment.…”
Section: Genetic Modifications Of Oncolytic Adenovirusmentioning
confidence: 99%
“…In addition to IL-24 and IL-12, Sun et al investigated whether recombinant adenoviruses expressing IL-2 (rAd-IL-2) as a gene immunotherapy agent could optimize the prognosis of HCC patients (53). IL-2 treatment was the first immunotherapy approved by the US Food and Drug Administration for use in melanomas (105).…”
Section: Modulation Of the Host Immune Response Triggered By Oncolytimentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the efficacy of available treatments remains largely unsatisfactory. However, thanks to advances in stem cell transplantation therapies, the situation is gradually improving as increasing evidence suggests that the treatment of traumatic nervous system damage is possible (2729). Notably, the type of cell chosen is critical for the therapy efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Promising cytokine immunotherapies currently under investigation are pegylated INF [ 117 ], INF-β [ 118 ], IL-2 in adenoviral vector [ 119 ], IL-6 [ 120 ], IL-7 [ 121 ], TNF-α [ 122 ], and TGF-beta [ 123 ]. In addition, intracellular biosignaling pathways related to cytokines are also a promising approach [ 124 ].…”
Section: Modulating Il-1β and Il-18 As A Therapeutic Target In Hccmentioning
confidence: 99%